Gunstock Deformity of the Elbow: Clinical Features, Biomechanics, and Current Treatment Strategies: A Literature Review - Ihza Namira Athalia; Imey Pinasty Harianto Putri; Atriska Citra Muliana; Shira Shalsabina Shafitri; Janiya Abdila Ilmiah; Baiq Merna Merta Sari; Rashieka Salma Aulia; Gantha Narendra Josafat; Muhammad Hilmy As Shiddiq; I Nyoman Yudayana Indratama; Rangga Cahya Prasetya; Nurhidayati Nurhidayati (Indonesian Publication Center, 2026)
Gunstock deformity, also known as cubitus varus, is a common complication that arises after supracondylar humerus fractures in children, primarily due to malunion of the bone. This condition results in an inward deviation of the forearm when the elbow is in full extension, creating a pronounced change in contour that can significantly impact biomechanical function and the quality of life of the patient. Common clinical symptoms include pain on the lateral side of the elbow, limited range of motion, and joint instability, particularly associated with ulnar neuropathy. Diagnosis is established through physical examination and radiological imaging to identify the angle of deviation and malalignment. Management of this deformity varies based on severity, ranging from observation in mild cases to surgical interventions like osteotomy in more severe cases. Common corrective techniques include lateral closing wedge osteotomy and dome osteotomy, aimed at restoring anatomical alignment and preventing long-term complications. Postoperative rehabilitation is crucial for regaining joint function and muscle strength. Long-term prognosis is generally good; however, it requires appropriate management to avoid complications like joint stiffness and ulnar neuropathy. A comprehensive approach encompassing diagnosis, deformity correction, and rehabilitation is essential for achieving optimal functional outcomes.